Different vitamin K forms in hemodialysis patients: a simple dietary supplement to battle vascular calcification-randomized controlled trial - Howaida Abdelhameed Elshinnawy; Tamer Wahid El-Said; Sarah Farid Fahmy; Ahmed Shamseldin; Sherin Ibrahim; Reem Mohsen Elsharabasy (SpringerOpen, 2023)
Abstract Background and aim Vascular calcification is a significant risk factor for cardiovascular diseases in patients with end-stage renal disease, particularly those on hemodialysis. Previous research on vitamin K found that it had a positive on calcification markers. However, clinical data is still limited. This study aimed to compare the efficacy and safety of vitamin K2 versus vitamin k1 on a calcification regulator in hemodialysis patients. Methods A prospective randomized placebo-controlled trial was conducted on 120 patients, who were divided into three groups; group 1: administered 10 mg of vitamin K1 (phytomenadione thrice weekly); group 2: administered 90 μg of vitamin k2 (MK-7); group 3: administered placebo for 3 months. Matrix Gla protein (MGP), calcium, phosphorous, and intact parathyroid hormone levels were measured. Results MK-7 significantly increased active MGP levels compared to phytomenadione and placebo groups (p<0.0001). No correlations were found between calcium, phosphorous, PTH, and MGP levels at baseline or after treatment. Conclusion Vitamin k supplementation was effective and tolerable in modulating MGP in hemodialysis patients, with MK-7 outperforming phytomenadione.